Quantitative Analysis of Relationships Between Panicle Size and Fruit Traits in Litchi (Litchi chinensis Sonn.) - Lal, Narayan; Kumar, Abhay; Nath, Vishal (International Journal of Bio-resource and Stress Management, 2020)
An experiment was conducted to assess the effect of inflorescence on fruit set, yield and quality of three litchi cultivars viz., Rose Scented, Mandaraji and Seedless Late in 2017 and 2018 at ICAR-National Research Centre on Litchi, Muzaffarpur, Bihar. Panicle length determined fruit set in Rose Scented and Mandaraji, and panicle length and girth are important for fruit retention in Seedless Late. Results revealed that there was a strong correlation between the length and width of panicle in cultivar Rose Scented (0.989), Mandaraji (0.970) and Seedless Late (0.771). The length of panicle was highly and positively correlated with fruit set in cultivar Rose Scented (0.896), Mandaraji (0.955) and Seedless Late (0.943) and it was also positively and strongly correlated with girth of panicle in cultivar Rose Scented (0.763) and Seedless Late (0.966) and weakly correlated in Mandaraji (0.526). A strong correlation between girth of panicle with fruit set in both years was also observed in Rose Scented (0.882) and Seedless Late (0.940). A very strong correlation between girth of panicle and fruit weight was observed in Seedless Late (0.608) in both the year. The optimum girth of panicle was 4.23 mm in Mandaraji for higher fruit set. However, in Seedless Late, fruit set increased with increase in panicle length and girth. For genetic improvement in litchi, emphasis on length and girth of panicle should be given during selection of improved cultivars.